Paver blocks manufactured from construction & demolition waste. (2020) - Kumar, Gyanendra; Shrivastava, Sandeep; Gupta, R.C.
Abstract: Due to the limited availability of natural aggregates (NA), it is mandatory to find alternate of NA. In this study, I-shape 80 mm recycled paver blocks (RPBs) were manufactured in the factory and laboratory setup by replacing 10 mm (0%, 15%, 30%, 45%, 60% & 75%) natural coarse aggregates (NCA) by coarse recycled concrete aggregates (CRCA) derived from construction & demolition waste (C&DW). RPBs were subjected to visual inspection, dimension tolerance, compressive strength, water absorption and impact test and observed that CRCA can replace up to 60% natural aggregates in PBs and lab manufactured RPBs are better than factory manufactured.